In vitro study on the antimicrobial property of guava leaves extraction enterococcus faecalis - Cortez, Hazel M.; Lacbanes, Laurenn O.; Medina, Ma. Concepcion B. (Co-author).
Enterococcus faecalis is the microorganism predominantly found in secondary endodontic infections. The effective irrigant against this microorganism in 5.25% NaOCI. However, this is toxic to periapical tissues when extruded, and it weakens the dentin. Guava leaves extract (GLE), with proven antimicrobial activity, can be an alternative irrigant against Enterococcus faecalis. METHODS: Laboratory experimental design was employed. Eight different concentrations of GLE were prepared in test tubes and the minimum inhibitory concentration (MIC) was determined. Enterococcus faecalis was inoculated in 18 blood agar plates and exposed to the MIC of GLE (6g/5ml), to 8g/5ml and GLE, distilled water and 5.25% NaOCI at 6 different exposure times, and then the zone of inhibition was measured. Results: 6g/5ml is the MIC of GLE against Enterococcus faecalis. It did not produce any zone of inhibition. The mean ranks of zones of inhibition produced by 8g/5ml and 10g/5ml GLE are not comparable with that of 5.25% NaOCI using Mann Whitney test with p>0.05. There is no significant difference in the mean ranks at specific exposure times between groups. CONCLUSION: 8g/5ml and 10g/5ml GLE have antimicrobial activity against Enterococcus faecalis but is not comparable with 5.25% NaOCI. Exposure time has no effect on their antimicrobial activity.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.